Executive Function and Language Input: Neurological Insights from French Immersion Learners - Poliquin, Laurent; Moussa, Naziha Abakar (Current Journal of Applied Science and Technology, 2025)
This study examines how the consistency of French language input by teachers in immersion classrooms impacts both language acquisition and executive function in elementary students, including those with neurodivergent profiles. A cross-sectional observational study was conducted with 128 students aged 7–9 across five immersion schools in Winnipeg. Participants were grouped based on observed teacher language input consistency. Data included standardized cognitive and language assessments, parent surveys, and teacher evaluations using the BRIEF-2. Students receiving ≥90% French input outperformed peers in vocabulary, working memory, and inhibitory control. Neurodivergent students also demonstrated gains in high-consistency environments, though with greater variance. Findings support the cognitive benefits of immersion fidelity. However, rigid language policies may risk excluding vulnerable learners. The results call for adaptive strategies that combine linguistic consistency with inclusive pedagogy. Consistent French instruction enhances language and cognitive outcomes for diverse learners. Immersion policies must balance fidelity with flexibility to remain equitable and neurologically supportive.